Design of AI-based gamification platform for effective educational service using child behavior prediction/change (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the advancement of advanced technologies such as artificial intelligence, robots, autonomous vehicles, healthcare, virtual reality, augmented reality, etc. and the popularization of smartphones, it stimulates customer interest and leads voluntary participation in order to maximize interactive communication in all industries The gamification strategy incorporating games began to emerge. A representative field that generates results by easily introducing such a gamification strategy is the education industry that seeks to improve the educational effect by utilizing the elements of corporate marketing strategies and games such as challenge, competition, achievement, and reward. Recently, gamification research is being conducted to effectively apply AI and big data, the core technologies of the 4th industrial revolution in all industries. Gamification is actively forming markets in Europe and the US, and it can increase customer loyalty and productivity by applying various roles applied to games in other industries as well as serious games. The purpose of this study is to design and implement a gamification service platform based on artificial intelligence technology and operate the implemented system to expand the area where the gamification service applied to the existing marketing and consulting fields can be used. The designed gamification service platform can be applied to education services that increase learning efficiency by analyzing the predicted learning attitudes of trainees, and through successful research cases, it will be able to provide immersion effect to trainees and teaching method research to educators.